Biological seed treatment for the control of loose smut of wheat - V.K. MAHESHWARl, DHARAM SINGH and (Indian Phytopathology, 2002)
Loose smut of wheat caused by Ustilago segetum var. tritici was controlled almost completely through seed treatment with any of the bioagents like Trichoderma viride, T. harzianum; Pseudomonas fluorescence and Gliocladium virens in combination with vitavax @ 0.125% during three years of trial from 1996 to 1998. The values of smut control were even better than full dose of vita vax (0.25%). The per cent seed germination in the laboratory, seedling emergence in the field and seed yield per plot were significantly high due to integrated seed treatment with bioagents and vitavax.